Development of Fluvio-Lacustrine Systems in the Young Glacial Area in Poland Based on the Research in the Valleys of the Rivers Wierzyca and WDA - Błaszkiewicz, Mirosław (Quaestiones Geographicae, 2010)
Both rivers presented in the article, the Wierzyca River and the Wda River, flow along typical polygenic valleys in young glacial areas. Their valleys include a number of postglacial basins, mainly subglacial channels connected by gap sections. The course of fluvial processes in postglacial basins was determined by the Late Glacial melting and the development of lakes. In Holocene, on the lacustrine and delta deposits, which were filling up the lake basins, wide meander zones with meandering river beds developed. In Late Glacial erosive processes dominated at the gap sections, which ended up with the development of slide meanders. Since the beginning of Holocene, lateral erosion has been dominant due to stabilization of the river bed. This has lead to the widening of the floodplain. Despite this, along the major course of both valleys the width of the floodplains is insufficient for free development of river channels. This is the case of constrained meandering.